2010
DOI: 10.1093/rheumatology/kep463
|View full text |Cite
|
Sign up to set email alerts
|

Haem oxygenase-1 down-regulates high mobility group box 1 and matrix metalloproteinases in osteoarthritic synoviocytes

Abstract: We have provided direct evidence that HO-1 down-regulates MMP-1, -3 and HMGB1 in osteoarthritic synoviocytes. HO-1 may be a potential strategy to control inflammatory and degradative processes in the progression of OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 34 publications
2
20
1
Order By: Relevance
“…CSPCs have been observed in human, equine 54 and bovine 11 articular cartilage. Identification, isolation and characterization of CSPCs have been based on a | expression of stem-cell-related surface markers (individually and in combination, under various conditions) and b | properties such as clonogenicity and multipotency.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…CSPCs have been observed in human, equine 54 and bovine 11 articular cartilage. Identification, isolation and characterization of CSPCs have been based on a | expression of stem-cell-related surface markers (individually and in combination, under various conditions) and b | properties such as clonogenicity and multipotency.…”
Section: Figurementioning
confidence: 99%
“…31 For example, high mobility group protein B1 (HMGB1) released by OA synoviocytes has been implicated as a biochemical mediator of inflammation, acting in cooperation with IL-1β. 31,54 Other soluble factors could also enhance the chemotactic activity of chondrocytes, such as insulin-like growth factor 1 (IGF-1) in serum 55 and platelet-derived growth factor (PDGF) 55,56 in synovial fluid 57 or post-traumatic bleeding. 58,59 Thus, migration of CPCs is likely to be regulated by multiple tissue-injury-related signals.…”
Section: Function Of Cspcs In Cartilage Repairmentioning
confidence: 99%
“…Biliverdin and CO have anti-inflammatory properties. Increasing evidence suggests that loss of HO-1 increases HMGB1 release, whereas upregulation of HO-1 inhibits HMGB1 release in response to inflammatory stimulus (Chen et al, 2013b; Clerigues et al, 2012; Garcia-Arnandis et al, 2010a; Gong et al, 2008; Jang et al, 2012; Park et al, 2013; Sakai et al, 2012; Tsoyi et al, 2009; Wang et al, 2013g; Yun et al, 2010). …”
Section: Hmgb1 Releasementioning
confidence: 99%
“…CXCR3 −/− , but not CCR1 −/− , CCR5 −/− mice and NK cell-depleted mice display severe liver damage after CCl4 injection partly through increased HMGB1 expression in the liver (Zaldivar et al, 2012); HO1 −/− mice show increased mortality in sepsis partly through increased HMGB1 expression in response to LPS or IL-1β (Garcia-Arnandis et al, 2010a; Takamiya et al, 2009); PI3Kγ −/− mice ameliorated the LPS-induced decrease in myocardial contractility and HMGB1 mycocardial expression (Xu et al, 2010); Single-Ig-interleukin-1 related receptor (SIGIRR) −/− mice show cognitive deficiencies and hippocampal dysfunction with enhanced expression of HMGB1 (Costello et al, 2011); Metalloproteinase Zmpste24 −/− mice exhibit lipodystrophy with upregulated HMGB1 expression (Peinado et al, 2011). …”
Section: Hmgb1 Transcriptional Regulation (Figure 8)mentioning
confidence: 99%
“…Nevertheless, the pro-inflammatory activity of HMGB1 in synoviocytes and its participation in synovitis during OA remain to be determined. We have recently reported that HMGB1 is released by OA synoviocytes after activation with IL-1β [16], suggesting the participation of HMGB1 in the inflammatory response induced by this cytokine. In the present study, we further investigated the role of HMGB1 in OA synovial inflammation.…”
Section: Introductionmentioning
confidence: 99%